Exploration of Sandwich Generation Financial Behavior and Management in Surakarta - Pramesti, Vanika Ardhi; Jatmika, Surya (Universitas Muhammadiyah Pontianak, 2026)
This study explores the financial behavior and management strategies of the sandwich generation in Surakarta through a qualitative case study approach. Data were collected from seven individuals identified as part of the sandwich generation using in-depth interviews and documentation. The findings show that financial priorities include basic needs, education, and monthly bills, leaving limited room for savings or investment. Strategies used include savings, loans, and family support. The main challenges are limited income, financial stress, and emotional burdens. This study highlights the importance of financial literacy, long-term planning, and income diversification for enhancing financial resilience..